A Causal Relation Model of Market Orientation and Extended Market Orientation Factors Affecting Strategic through Performance for Thai Health Establishments in Bangkok - Nakkhasin, Wirut; Punyasiri, Sangkae; Suksawang, Poonpong (Journal of Cultural Approach, 2019)
The research was done in Bangkok, Thailand due to high competition and the The research was done in Bangkok, Thailand due to high competition and the presence of a majority of Thailand’s health establishments, which aims 1) to review market orientation, extended market orientation and strategic management affecting health establishment performance in Bangkok 2) to study the relationship between market orientation, extended market orientation and strategic management affecting health establishment performance in Bangkok 3) to investigate of concept for causal relation model of market orientation and extended market orientation effecting health establishment performance in Bangkok. Research method of this study is a mixed methods research methodology, which quantitative and qualitative approaches. The population is Thailand’s health establishments managers. Sample size was 412 managers, derived using statistical methods to determine a size which yields validity and reliability. The results revealcausal relationship model between market orientation, extended market orientation, strategic management, and health establishment performance as follow structured equation: SM = 0.84MO + 0.40EMO and PER = 0.80SM